Sport foods and dietary supplements for optimal function and performance enhancement in track-and-field athletes - Peeling, P.; Castell, L. M.; Derave, W.; de Hon, O. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Athletes are exposed to numerous nutritional products, attractively marketed with claims of optimizing health, function, and performance. However, there is limited evidence to support many of these claims, and the efficacy and safety of many products is questionable. The variety of nutritional aids considered for use by track-and-field athletes includes sports foods, performance supplements, and therapeutic nutritional aids. Support for sports foods and five evidence-based performance supplements (caffeine, creatine, nitrate/beetroot juice, ß-alanine, and bicarbonate) varies according to the event, the specific scenario of use, and the individual athlete`s goals and responsiveness. Specific challenges include developing protocols to manage repeated use of performance supplements in multievent or heat-final competitions or the interaction between several products which are used concurrently. Potential disadvantages of supplement use include expense, false expectancy, and the risk of ingesting banned substances sometimes present as contaminants. However, a pragmatic approach to the decision-making process for supplement use is recommended. The authors conclude that it is pertinent for sports foods and nutritional supplements to be considered only where a strong evidence base supports their use as safe, legal, and effective and that such supplements are trialed thoroughly by the individual before committing to use in a competition setting. Abstract from author